Demography, Development and Control of the Coastal Space on the Pacific Coast of Mexico - Graciela Alcalá (CUHSO)
During the four final decades of the last century, demographicgrowth in Mexico slowed significantly. This trend continued during the firstdecade of the 21st century, in tune with current expectations in the country.However, during precisely the same decades, the opposite phenomenon hasbeen occurring in the country’s coastal territories, i.e. demographic growthresulting not from an increase in average birth rates, which have followedmore or less the same trends as among the rest of the country’s inhabitants,but from immigration into these areas. This phenomenon is of itself reliableproof of the growth in investment of both public and private capitalin coastal territories. The only exception to this trend is provided by threecoastal municipalities in the state of Sinaloa, created in the early 1990s andtaken over, literally, by drug-trafficking activities. The vast majority of thesenew inhabitants of the Mexican coastlines are people who have arrivedfrom inland in search of jobs, in the hope of improving their lives. For thenew «costeños», life in these latitudes is completely different to that whichthey had experienced in their previous homes, whether in the plateau orthe central plain, the deserts of the north, the limestone country of the interiorof the Yucatán peninsula or the tortuous hillsides of the mountains:new rhythms and ways of working, different local eating habits and modesof dress, unknown climatic phenomena and their consequences for dailylife, strange idiomatic expressions, and finally the exotic affection of the native «costeños» for their countryside and their local flora and fauna. Toanalyse the case study, we propose the concept of the «coastal region». Weuse demographic information both at national level and from the coastalstates and municipalities, taken from national censuses of population andhousing done in the decades from 1950 to 2010, published by the InstitutoNacional de Estadísticas, Geografía e Informática (National Institute ofStatistics, Geography and it, inegi), as well as photographs from variousarchives and from the author’s collection. It is not appropriate to talk of an«experimental design» in this work, since it is not an «experiment» but anattempt to explain what has been happening among the inhabitants of theMexican coasts on the basis of the developing situation over some 50 yearsof constant colonisation.